The crystal structure of 3,5-bis(propan-2-yl)-1H-pyrazol-4-amine, C9H17N3 - Fujisawa, Kiyoshi; Ageishi, Keigo; Okano, Mitsuki; Tiekink, Edward R. T. * (De Gruyter Open, 2022)
C9H17N3, monoclinic, P21/c (no. 14), a = 9.5601(3) Å, b = 9.5210(3) Å, c = 10.7651(3) Å, β = 94.564(3)°, V = 976.75(5) Å3, Z = 4, Rgt(F) = 0.0432, wRref(F2) = 0.1223, T = 178(2) K. CCDC no.: 2202375 The crystal structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.